Electronic Health Record User Dashboard for Optimization of Surgical Resident Procedural Reporting - Evans, Parker T.; Nelson, Scott D.; Wright, Adam; Aher, Chetan V. (Applied Clinical Informatics, 2025)
Background While necessary and educationally beneficial, administrative tasks such as case and patient tracking may carry additional burden for surgical trainees. Automated systems targeting these tasks are scarce, leading to manual and inefficient workflows.Methods We created an electronic health record (EHR)-based, user-specific dashboard for surgical residents to compile resident-specific data: bedside procedures performed, operative cases performed or participated in, and notes written by the resident as a surrogate for patients cared for. Usability testing was performed with resident volunteers, and residents were also surveyed postimplementation to assess for efficacy and satisfaction. Access log data from the EHR was used to assess dashboard usage over time. Descriptive statistics were calculated.Results The dashboard was implemented on a population of approximately 175 surgical residents in 5 different departments (General Surgery, Obstetrics and Gynecology, Neurosurgery, Orthopaedics, and Otolaryngology) at a single academic medical center. Six resident volunteers participating in usability testing completed an average of 96% of preset tasks independently. Average responses to five questions extracted from the System Usability Scale (SUS) questions ranged from 4.0 to 4.67 out of 5. Postimplementation surveys indicated high resident satisfaction (4.39 out of 5) and moderate rates of use, with 46.4% of residents using the dashboard at least monthly. Daily use of the dashboard has increased over time, especially after making the dashboard a default for surgical residents.Conclusion An EHR-based dashboard compiling resident-specific data can improve the efficiency of administrative tasks and supplement longitudinal education.
Keywords: surgery; residents; surgical education; electronic health record; Epic; dashboard; case logging